THE EFFECT OF THE POWER OF TWO LEARNING STRATEGY ON STUDENTS’ PERFORMANCE IN BIOLOGY LEARNING - Dini Afriansyah; Anita Restu Puji Raharjeng; Irham Falahudin; Nyimas Amalia (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study aims to determine the effect of learning strategy the power of two on the activity of students in Biology learning. This research design uses posttest-only control design with quasi experimental method. The population in this study is the entire class in X class in one high school at Palembang consisting of 5 classes, with 141 students. Sampling is using purposive technique. The sample of this study is X IPA 3 class with 36 students as experimental class and X IPA 2 class with 36 students as control class. In the learning process, the experimental class is taught by using the power of two learning strategy and control class using conventional method (lecture). Data collection is from observation sheet and questionnaire of student learning activity which have been tested its validity by using Aiken's V formula. The result of this study shows that the average of student learning activity in the experimental class in 2 meetings is 83,05% of the students who have been active in very active category. In control class, the percentage of active students 55,46% is active category. Result of data analysis that is using t-test with significant level 0,05 obtained tarithmetic = 9,693 while ttable = 1,994 seen that tarithmetic > ttable. Therefore, Ha is accepted and H0 is rejected thus it can be concluded that the power of two's learning strategy can have an effect on student's learning activeness. Increasing the liveliness of learners can optimize the motivation, cooperation, responsibility, reading interest, and learner activity in the learning process. Keywords: learning strategy, learning, the power of two, student activity